Improvement of In Vitro Osteogenic Potential through Differentiation of Induced Pluripotent Stem Cells from Human Exfoliated Dental Tissue towards Mesenchymal-Like Stem Cells - Felipe Augusto Andre Ishiy; Roberto Dalto Fanganiello; Karina Griesi-Oliveira; Angela May Suzuki; Gerson Shigeru Kobayashi; Andressa Gois Morales; Luciane Portas Capelo; Maria Rita Passos-Bueno (Hindawi Limited, 2015)
Constraints for the application of MSCs for bone reconstruction include restricted self-renewal and limited cell amounts. iPSC technology presents advantages over MSCs, providing homogeneous cellular populations with prolonged self-renewal and higher plasticity. However, it is unknown if the osteogenic potential of iPSCs differs from that of MSCs and if it depends on the iPSCs originating cellular source. Here, we compared the in vitro osteogenesis between stem cells from human deciduous teeth (SHED) and MSC-like cells from iPSCs from SHED (iPS-SHED) and from human dermal fibroblasts (iPS-FIB). MSC-like cells from iPS-SHED and iPS-FIB displayed fibroblast-like morphology, downregulation of pluripotency markers and upregulation of mesenchymal markers. Comparative in vitro osteogenesis analysis showed higher osteogenic potential in MSC-like cells from iPS-SHED followed by MSC-like cells from iPS-FIB and SHED. CD105 expression, reported to be inversely correlated with osteogenic potential in MSCs, did not display this pattern, considering that SHED presented lower CD105 expression. Higher osteogenic potential of MSC-like cells from iPS-SHED may be due to cellular homogeneity and/or to donor tissue epigenetic memory. Our findings strengthen the rationale for the use of iPSCs in bone bioengineering. Unveiling the molecular basis behind these differences is important for a thorough use of iPSCs in clinical scenarios.